The indirect effects of perfectionism on athletes’ self-views through maladaptive emotion regulation - Minichiello, Hollie; Reasonover, Madisen; Fuglestad, Paul (Frontiers in Psychology, 2024)
Introduction In general, increased levels of perfectionism have been associated with increased levels of burnout, heightened levels of depression and anxiety, lowered self-esteem, and poorer overall performance, yet perfectionistic strivings within athletes have also been associated with lower burnout and better performance in some contexts. Methods The current study investigated whether emotion regulation strategies would indirectly link perfectionism with self-esteem in young adults who had participated in competitive athletics. Two hundred and fifty-three primarily white (60.0 %), female (83.0 %) undergraduate students who had participated in competitive athletics completed a series of questionnaires including: the Self-liking and Self-Competence Scale – Revised, the Cognitive Emotion Regulation Questionnaire, and the short form of the Multidimensional Perfectionism Scale. Results The PROCESS macro for SPSS was used to examine the indirect association between perfectionism and self-esteem through emotion regulation. Higher self-oriented perfectionism and socially prescribed perfectionism were both indirectly associated with lower self-liking and self-competence through greater catastrophizing and self-blame. Discussion For individuals like athletes, who experience internal and external pressures, increased perfectionism may lead to negative self-views through maladaptive emotion regulation. However, longitudinal and experimental work is needed to establish this proposed pattern of relationships.